The Image of Marriage Migrants in the Media of South Korea (for example «Chosun Ilbo») (Journal of Oriental Studies, 2016)
In this paper an attempt is made on the basis of a random sample of Internet archive of one of the major daily newspapers in South Korea, «Chosun Ilbo» to confirm or refute existing theories about stereotypes in relation to marriage migrants in South Korea.
Keywords: South Korea; marriage migrants; multiculturalism; the media stereotype